2018
DOI: 10.1089/tmj.2017.0089
|View full text |Cite
|
Sign up to set email alerts
|

Providing Dementia Consultations to Veterans Using Clinical Video Telehealth: Results from a Clinical Demonstration Project

Abstract: Video consultation was well accepted by both dementia patients and caregivers. CVT may facilitate timely diagnosis and management and provide support for rural dementia patients and caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 34 publications
5
46
0
9
Order By: Relevance
“…The present study aimed to examine the acceptability and feasibility of a longitudinal technology-driven care management program employing wearable technology and monthly telehealth visits with a neuropsychologist in a sample of individuals with advanced dementia. Consistent with previous studies, we found high acceptability by both the residents and their caregivers (Dang et al, 2018;Farina & Lowry, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The present study aimed to examine the acceptability and feasibility of a longitudinal technology-driven care management program employing wearable technology and monthly telehealth visits with a neuropsychologist in a sample of individuals with advanced dementia. Consistent with previous studies, we found high acceptability by both the residents and their caregivers (Dang et al, 2018;Farina & Lowry, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…exploring issues of usability and acceptability). 45,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Many focus specifically on the clinical use of Skype, 91,[114][115][116][117][118][119][120][121][122][123] either on its own or in combination with other technologies [e.g. WhatsApp (WhatsApp Inc., Mountain View, CA, USA) messaging 124 or FaceTime 125,126 ].…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
“…Other studies have shown similar levels of patient satisfaction, particularly in terms of time saved (as a result of not needing to travel to clinics) and costs saved. 101,104,107 In a randomised trial of Skype sessions versus standard home care in supporting families with premature infants, the nine families randomised to Skype sessions reported very positive experiences. All found the technology easy to use, noting that virtual consultations were better than telephone calls.…”
mentioning
confidence: 99%
“…Although we are not aware of any study reporting the use of telehealth for tinnitus management during the COVID-19 pandemic, there has been widespread availability of telehealth services for audiology (Swanepoel and Hall 2010;Tao et al 2018), and this increased during the lockdown (Huang, Imam, and Nguyen 2020;Ratanjee-Vanmali, Swanepoel, and Laplante-L evesque 2020). Even prior to the lockdown, several authors suggested the use of therapy for tinnitus via telephone, Internet or hard copy educational materials (Molini-Avejonas et al 2015;Aazh, Moore, and Roberts 2009;Beukes et al 2018b;Dang et al 2018;Henry et al 2019).…”
Section: Discussionmentioning
confidence: 99%